MENINGKATKAN KETERAMPILAN BERBICARA SISWA BELAJAR BAHASA INGGRIS MELALUI PENGGUNAAN MEDIA PEMBELAJARAN UNDANGAN ( INVITATION ) PADA SISWA KELAS VIII - Agustinawati Agustinawati (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The background of this study was that students were still weak in correct speaking, and students were inconsistent in pronouncing a vocabulary. This study aims to improve the speaking skills of students learning English through the use of invitation learning media for class VIII.A students of SMP Negeri 3 Muara Bungo. This type of research is a classroom action research conducted in two cycles. The results showed that the use of invitation learning media (invitation) could improve students' speaking skills with an average speaking skill of students learning English in the first cycle was 66 and the second cycle was 78